2016
DOI: 10.1159/000452587
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renalase is Not Associated with Blood Pressure and Brachial-Ankle Pulse Wave Velocity in Chinese Adults With Normal Renal Function

Abstract: Background/Aims: This study aimed to investigate the association of renalase with blood pressure (BP) and brachial-ankle pulse wave velocity (baPWV) in order to better understand the role of renalase in the pathogenesis of hypertension and atherosclerosis. Methods: A total of 344 subjects with normal kidney function were recruited from our previously established cohort in Shaanxi Province, China. They were divided into the normotensive (NT) and hypertensive (HT) groups or high baPWV and normal baPWV on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Wang et al . reported that the eGFR was associated with decreased odds of a high baPWV (OR 0.974, P = 0.04) in 344 Chinese adults 34 . In their study, people with high baPWV showed higher urine albumin-to-creatinine ratio (7.52 mg/g) than those with normal baPWV (vs. 6.07 mg/g, P = 0.021), but the significance was not maintained in multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al . reported that the eGFR was associated with decreased odds of a high baPWV (OR 0.974, P = 0.04) in 344 Chinese adults 34 . In their study, people with high baPWV showed higher urine albumin-to-creatinine ratio (7.52 mg/g) than those with normal baPWV (vs. 6.07 mg/g, P = 0.021), but the significance was not maintained in multivariate logistic regression analysis.…”
Section: Discussionmentioning
confidence: 97%
“…Alcohol consumption was defined as subjects who claimed that they consumed alcohol (liquor, beer, or wine) every day and that consumption lasted for 6 months [27]. Blood pressure (BP) was measured in the sitting position using a standard mercury sphygmomanometer as previously described [28][29][30][31]. Hypertension was defined as a systolic BP of ≥140 mm Hg, a diastolic BP ≥ 90 mm Hg, or as the use of antihypertensive agents according to subjects' self-report or pharmacy data.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Such contradictory results can be attributed to the fact that all currently existing methods for quantitative determination renalase are based on employment of various antibodies . Reasons for these differences in the antibody‐based evaluations of renalase levels have been considered by Desir and Peixoto and provoked serious concerns about ‘proper interpretation’ of plasma renalase levels ‘especially in patients with kidney disease’ . These include insufficient specificity of generated antibodies to renalase and their interaction not only with full‐length renalase, but also with renalase‐derived products of both degradation and aggregation …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Reasons for these differences in the antibody-based evaluations of renalase levels have been considered by Desir and Peixoto 5 and provoked serious concerns about 'proper interpretation' of plasma renalase levels 'especially in patients with kidney disease' . 13 These include insufficient specificity of generated antibodies to renalase and their interaction not only with full-length renalase, but also with renalase-derived products of both degradation and aggregation. 5,13 Thus there is a clear need for antibody-free methods of renalase detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation